Mesoscale convective precipitation system modified by urbanization in Beijing City - Guo, Xueliang; Fu, Danhong; Wang, Jing (Atmospheric research, 2006)
The possible effect of urbanized modification on cloud structure and precipitation distribution in a severe convective precipitation system on June 4, 2003 in Beijing City was numerically investigated by using the PSU/NCAR Mesoscale Modeling System (MM5). To reflect the rapidly changed surface condition in Beijing City due to its explosive growth of the urban population, the city land surface used in model was modified by increasing land surface roughness length and albedo, and decreasing thermal inertia and moisture availability according to the urban surface characteristics. The results show that after the urbanized modification the surface sensitive heat flux increases and concentrates, while the surface latent heat flux reduces remarkably due to the decrease of moisture availability. The convective cells occur earlier and distribute dispersedly as suggested in previous studies, but the cloud peak updraft decreases, and downdraft is intensified, which should be attributed to the effect of the decreased moisture in the urbanized region. The upper convection weakens and the lower convection strengthens, due primarily to the increase of surface roughness over land that enhances the lower convergence. The total accumulated precipitation in the whole domain decreases, especially in the urbanized region, and its distribution tends to become concentrated and also intensified along the borderline between urban and non-urban region. The precipitation intensity is also modified and locally distributed, and the high precipitation intensity core is found downwind of the city. The peak rainfall located near borderline is 40 mm for the non-urbanized condition and 65 mm for the urbanized condition. The simulated precipitation intensity and distribution after modification are more consistent with those observed in this region. Thus, the urban region could act to create a bifurcation zone for precipitation distribution and produce more floods as suggested by early studies.